Pravna analiza pogodbe o računalništvu v oblaku - Pirnat, Tadeja (Pravnik, 2015)
Many studies and papers analyze cloud computing from various points of views. However, all the very inspiring practical proposals could be about trust, confidence and dependence. Trust to put one's content in the cloud, confidence to obtain the benefits requested of such pay-per-use on-demand IT service and, finally, dependence on all the risks such IT deployment models of storage and memory space bear. Understanding the cloud computing stack, this type of -ing contract can be knotty and as such completely neglected by the Slovene regulation, although constantly under the radar by various European expert groups. This article examines the specific structure of cloud computing contract in view of the existing national legislation. In particular, the article answers the following questions: What is the legal nature and the form of the contract? What are the consequences of the so-called click wrap method? What is the purpose of various policies and smart disclosure in cloud computing contract? What is the type of obligation in the contract, of result or of means? Liability of cloud provider? How to interpret the so-called boiler plate clauses under the Slovene law? Finally, all consumers are informed how to overcome the significant contractual imbalances due to adhesion to cloud computing contracts by clicking the "I accept" button. What is yours, stays yours!
Keywords: informacijska tehnologija; informacijsko-komunikacijska tehnologija; information and communications technology; information technology; podatki; pogodbe; pravna ureditev; računalništvo v oblaku; varstvo podatkov